The use of songs to increase the learning of the english vocabulary among seventh year students, in parallel A at Pompilio Reinoso Jaramillo educational center, during the school year 2013-2014 - Elizalde Rojas, Andrea Stefania (2015)
This study is a descriptive research that was carried out with twenty seventh-A year students at “Pompilio Reinoso Jaramillo” Educational Center. The principal purpose of the action research work was to increase the English vocabulary through the use of songs. Therefore, some instruments such as tests, questionnaires, and a teacher field diary made by the researcher were designed to measure the progress and students´ perception. The results obtained by these instruments indicated that songs increment meaningfully the student’s vocabulary which was reflected in the raise of the post-test scores. Likewise, the answers received from the questionnaires confirmed the progress, enthusiasm and the positive attitude toward working with songs. In conclusion, this study facilitated the students to increase their vocabulary, the researcher to sharpen her teachings skills and the community to have a well-prepared teacher.